From cell membrane to the nucleus: an emerging role of E‐cadherin in gene transcriptional regulation. Issue 9 (28th August 2014) - Du, Wenjun; Liu, Xi; Fan, Guiling; Zhao, Xingsheng; Sun, Yanying; Wang, Tianzhen; Zhao, Ran; Wang, Guangyu; Zhao, Ci; Zhu, Yuanyuan; Ye, Fei; Jin, Xiaoming; et al.
Abstract E‐cadherin is a well‐known mediator of cell–cell adherens junctions. However, many other functions of E‐cadherin have been reported. Collectively, the available data suggest that E‐cadherin may also act as a gene transcriptional regulator. Here, evidence supporting this claim is reviewed, and possible mechanisms of action are discussed. E‐cadherin has been shown to modulate the activity of several notable cell signalling pathways, and given that most of these pathways in turn regulate gene expression, we proposed that E‐cadherin may regulate gene transcription by affecting these pathways. Additionally, E‐cadherin has been shown to accumulate in the nucleus where documentation of an E‐cadherin fragment bound to DNA suggests that E‐cadherin may directly regulate gene transcription. In summary, from the cell membrane to the nucleus, a role for E‐cadherin in gene transcription may be emerging. Studies specifically focused on this potential role would allow for a more thorough understanding of this transmembrane glycoprotein in mediating intra‐ and intercellular activities.